Tunable topologically driven Fermi arc van Hove singularities - Sanchez, Daniel S. S.; Cochran, Tyler A. A.; Belopolski, Ilya; Cheng, Zi-Jia; Yang, Xian P.; Liu, Yiyuan; Hou, Tao; Xu, Xitong; Manna, Kaustuv; Shekhar, Chandra; Yin, Jia-Xin; Borrmann, Horst; et al. (Nature Physics, 2023)
The classification scheme of electronic phases uses two prominent paradigms: correlations and topology. Electron correlations give rise to superconductivity and charge density waves, while the quantum geometric Berry phase gives rise to electronic topology. The intersection of these two paradigms has initiated an effort to discover electronic instabilities at or near the Fermi level of topological materials. Here we identify the electronic topology of chiral fermions as the driving mechanism for creating van Hove singularities that host electronic instabilities in the surface band structure. We observe that the chiral fermion conductors RhSi and CoSi possess two types of helicoid arc van Hove singularities that we call type I and type II. In RhSi, the type I variety drives a switching of the connectivity of the helicoid arcs at different energies. In CoSi, we measure a type II intra-helicoid arc van Hove singularity near the Fermi level. Chemical engineering methods are able to tune the energy of these singularities. Finally, electronic susceptibility calculations allow us to visualize the dominant Fermi surface nesting vectors of the helicoid arc singularities, consistent with recent observations of surface charge density wave ordering in CoSi. This suggests a connection between helicoid arc singularities and surface charge density waves.
CRIS-Team Scopus Importer:2023-03-20